Nothing Human Can Be Alien to Me. An Approach to the Historiography on the University History in Spain - Ruiz Carnicer, Miguel Ángel (CIAN-Revista de Historia de las Universidades, 2017)
The present work deals with the development of the study of the history of universities in Spain in terms of periods and themes, and tries to reflect how the intellectual, scientific, student and political aspects that surround the university institution have been approached. I revise the contributions of the different academic areas from their very beginning, focusing on the unique personalities who promoted this specialization, the creation of journals linked to this area and the celebration of congresses, pointing out the most relevant aspects of this contribution of Spanish historiography to the history of European Universities.
Keywords: Spain; history of universities; historiography; education